KOMPOSISI JENIS DAN POTENSI ANCAMAN TUMBUHAN ASING INVASIF DI TAMAN NASIONAL GUNUNG HALIMUN-SALAK, JAWA BARAT - Sunaryo Sunaryo; Tahan Uji; Eka Fatmawati Tihurua (Research Center for Biology-Indonesian Institute of Sciences, 2012)
A study on species composition and threat potential of invasive plant species was conducted in the Gunung Halimun-Salak National Park,Cidahu Resort, West Java. We developed two plots of different altitudes. The result showed that there were four invasive alien species possessing potential threat to the ecosystem and native species in the National Park, i.e. Piper aduncum (Piperaceae, with an Important Value of 20,70); Calliandra calothyrsus (Mimosaceae, IV = 9,11), Austroeupatorium inulaefolium (Asteraceae, IV = 18,77), and Clidemia hirta (Melastomataceae) as shrub. The threats of invasive plants happen in open forest area and could occur from the residential or public places.